2017
DOI: 10.1155/2017/8430907
|View full text |Cite
|
Sign up to set email alerts
|

Does Microscope Assistance in Cold Steel Tonsillectomy Reduce the Risk of Postoperative Hemorrhage? Results of a Prospective Cohort Study

Abstract: Background Posttonsillectomy hemorrhage (PTH) is the most feared complication. Dissection near the tonsillar capsule under microscopic view (TEmic) could be assumed to decrease PTH compared to traditional tonsillectomy (TEtrad). Methods In this study, patients were evaluated with respect to the need for surgical control (R/N: return/no return to theater (RTT): the day of surgery [0] or thereafter [1]). The findings at resection site and pain were measured. Results 869 patients were included (183 TEmic; 686 TEt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…More recently, lasers, coblation, and harmonic scalpel were utilized for tonsillectomy. 3 Tong et al did not report a single case of primary haemorrhage in their study of 90 tonsillectomies. 4 Robb et al concluded that perioperative use of Tranexemic acid reduces primary haemorrhage.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…More recently, lasers, coblation, and harmonic scalpel were utilized for tonsillectomy. 3 Tong et al did not report a single case of primary haemorrhage in their study of 90 tonsillectomies. 4 Robb et al concluded that perioperative use of Tranexemic acid reduces primary haemorrhage.…”
Section: Discussionmentioning
confidence: 94%
“…Fatal postoperative haemorrhage has been reported to a range between 0.2 and 1.0 per 10,000 performed procedures resulting in an average of 0.9 : 10,000. 3 Over the past four decades lot of efforts have been made to minimize the risk of post tonsillectomy haemorrhage in this surgical procedure. Surgical techniques employed to minimse haemorrhage are monopolar and bipolar dissection, CO2 laser, Coblation, and BiClamp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation